Changing structures induce changing behaviour. Streetscape revitalisation and human mobility. - Brezina, Tadej; Emberger, Günter (My University, 2017)
Der Beitrag erörtert die Möglichkeiten, duch eine Veränderung des Straßen- und Verkehrsbildes hin zu einer menschenzentrierten Gestaltung des urbanen Raumes das Mobilitätsverhalten und die Bewegungsmuster der Verkehrsteilnehmer zu verändern.

Designing transport infrastructures and urban streetscapes poses an ethical challenge for the human being a part of a socio-technical regime. Not only are humans of course in every stage of life and health every-day users of these designed structures, some also act as planning agents of the very same - either as planners or in a public participation. Densely intertwined with the ethics question of properly designing urban mobility structures is the question on where and how to start the change of structures. Overcoming mental barriers among planners and decision makers as well as users not yet accustomed to a changed streetscape pose a considerable challenge for shaping society's dynamically evolving urban transport regimes. Human mobility behaviour is subject to "fast "adaptability, if change management techniques are applied, ie. comprehensive information is available on a wide scale beforehand of the intervention. As large scale sporting events of the past have shown, such quasi-permanent transformation (closures for vehicular traffic) evoke the transport system's flexibility in reacting on such events: mobility patterns adapt. Because this paper claims to provide a synopsis of evidence and examples of changes in behaviour due to changed structures, it culminates with four sets of examples following these main lines of thought: (1) Example: Active modes friendly settlement structures (2) Example: Commuting infrastructure (3) Example: Parking place pricing and and locations (4) Example: Redifining road space usage. We conclude with highlighting the behavioural flexibility of mobility, the impacts of such behavioural changes from the urban dwellers' perspectives and the importance of making such changes conceivable beforehand.
Keywords: Stadtraum; Straßenraum; Stadtgestaltung; Straßengestaltung; Verkehrsinfrastruktur; Mobilität; Verhaltensmuster; Strukturwandel; Mobilitätsverhalten; Bewegungsmuster